Dynastic Politics in Regional Elections: Challenges to Democracy and the Need for Legal Reform in Indonesia: Politik Dinasti dalam Pemilihan Kepala Daerah: Tantangan terhadap Demokrasi dan Urgensi Reformasi Hukum di Indonesia - Mutawalli Mukhlis, Muhammad; Ilmar, Aminuddin; Maskun, Maskun; Aswanto, Aswanto; Tajuddin, Muhammad Saleh (Jurnal Konstitusi, 2024)
Dynastic politics, practiced by certain groups of individuals with kinship ties or close relationships, dominate political positions in regional head elections and local government administration processes. This phenomenon persists due to the lack of concrete regulations, thereby normalizing it as a political practice in Indonesia. This study aims to elaborate on the facts surrounding dynastic political practices, examine how such practices undermine the democratic ideals envisioned by the people, and propose prospective regulatory frameworks to address this issue. The research employs a normative juridical method with statutory, historical, and conceptual approaches. The findings reveal that dynastic political practices harm the democratic system and tend to be more formalistic rather than providing a genuine opportunity for the people to elect leaders aligned with their will. To prevent such practices in the future, the government, the legislature, and election organizers must collaborate to formulate concrete regulatory norms in the Regional Head Election Law.